SOIL DEGRADATION OF IRRIGATED PLAINS OF DAGESTAN AND WAYS OUT OF THE SITUATION - M. R. Musaev; Z. M. Musaeva; A. A. Magomedova (Юг России: экология, развитие)
Aim. The aim is to select the crops to reclaim the highly saline soils of the plains of Dagestan.Materials and Methods. We made an analysis of the literature sources; applied the field experiment methods using standard techniques, instruments and equipment along with processing of experimental data and mathematical statistics methods.Results. According to the results of the research held in agricultural production cooperative "Novaya Zhizn" of Kazbekski district, wheatgrass (Elytrigia elongata) formed higher rates of leaf area, photosynthetic potential of crops and net photosynthetic productivity. In the year of planting alfalfa, the yield amounted to 11.8; 14.0 and 11.7 t / ha which is less than the Elytrigia elongata for 22.8; 7.8 and 15.4%. A similar situation occurred in the second and third years of growth of perennial grasses. On average, during the years of research, productivity of Elytrigia elongate was higher compared with alfalfa respectively by 36.8; 20.1 and 40.7%.Conclusion. These studies indicate the effectiveness of growing Elytrigia elongata as a phytomeliorant on saline soils, as compared with alfalfa. Growing Elytrigia elongata on highly saline meadow soils is an effective technique to improve its structure.